Company-specific Characteristics and Market-driven Fixed Asset Revaluation in an Emerging Asian Economy / Md. Tahidur Rahman and Syed Zabid Hossain - Rahman, Md. Tahidur; Hossain, Syed Zabid (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
This study aimed to explore the company-specific and market factors driving fixed asset revaluation (FAR) in an emerging economy. Our research was based on a sample of 142 companies listed on the Dhaka Stock Exchange (DSE) - the main bourse of Bangladesh. The binary logistic regression model was the main instrument used to measure the significance level of variables and test the hypotheses. The study found that market conditions, profitability, nationality, debt-to-asset ratio, fixed assets intensity, and company size could influence FAR decisions significantly. But, company age and current ratio have failed FAR decisions insignificantly. Since there are suspicions about the creative practice of FAR, users need to be cautious when explaining and utilizing the information communicated via financial statements of companies that revalued their assets. Besides, regulators should strictly enforce the laws to avoid selective disclosures, and companies should fully disclose market-sensitive information so that corporate stakeholders promptly receive FAR-related disclosures. This paper could serve a large assortment of stakeholders interested in knowing the drivers behind and effects of FAR. Inclusion and the explanation of three new factors, corporate nationality, age, and market condition, could be an extension of the existing FAR literature.